1984
DOI: 10.1103/physrevlett.53.1133
|View full text |Cite
|
Sign up to set email alerts
|

Occupation Probabilities of Shell-Model Orbits in the Lead Region

Abstract: The occupation probabilities of shell-model orbits in the lead region are estimated by the addition of random-phase-approximation corrections to nuclear-matter results. The occupation probabilities of single-particle states in shells just below and above the Fermi energy are found to be ~ 0.7 and 0.1, respectively. It is shown that these estimates explain the quenching of the single-particle contribution observed in many elastic and inelastic electronscattering experiments.PACS numbers: 21.60. Cs, 27.80. + W S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
68
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(79 citation statements)
references
References 17 publications
11
68
0
Order By: Relevance
“…4.6 for the fully self-consistent results. The latter results formed the basis of the now corroborated prediction [54,146,147] for the occupation numbers in 208 Pb [143].…”
Section: Saturation Of Nuclear Matter From Short-range Correlationsmentioning
confidence: 64%
“…4.6 for the fully self-consistent results. The latter results formed the basis of the now corroborated prediction [54,146,147] for the occupation numbers in 208 Pb [143].…”
Section: Saturation Of Nuclear Matter From Short-range Correlationsmentioning
confidence: 64%
“…We present a combined analysis of inelastic electron-scattering data and electron-induced proton knockout measurements in an effort to obtain phenomenological information on nucleon-nucleon correlations. Our results indicate that the ratio of radial wave functions extracted from precise 10 B͑e, e 0 ͒ and 10 B͑e, e 0 p͒ measurements evolve from an interior depression for small E m , characteristic of short-range correlations, to a surface-peaked enhancement for larger E m , characteristic of longrange correlations. This observation can be interpreted in terms of the nucleon effective mass.…”
Section: (Received 22 August 1997)mentioning
confidence: 84%
“…Thus, if h e,e 0~m k ͑r͒͞m and h e,e 0 pm ‫ء‬ ͑r, E m ͒͞m, we would expect to find that the ratio of radial functions extracted from ͑e, e 0 ͒ and ͑e, e 0 p͒ experiments resembles the E mass, such that k͑r, E m ͒m E ͑r, E m ͒͞m. The 10 B͑e, e 0 p͒ data employed to investigate these ideas were taken from an experiment performed at the medium-energy electron accelerator at NIKHEF. The energy, duty factor, and average current of the beam were 407.3 6 0.2 MeV, 1%, and 1.5 mA, respectively.…”
Section: (Received 22 August 1997)mentioning
confidence: 99%
“…These measurements were brought together in a coherent picture by Pandharipande, Papanicolas and Wambach [14] who showed that the combination of nuclear matter and random-phase approximation calculations shown in Fig. 3 could explain the occupation probabilities of single particle orbitals in the Pb region.…”
mentioning
confidence: 99%
“…FIGURE 3. Calculated occupation numbers for single particle and hole states near the Fermi surface in Pb [14]. The dashed curve is a nuclear matter calculation including short-range correlations (long dashed) and long-range correlations and the points (crosses for proton statea and circles for neutron states) include RPA correlations.…”
mentioning
confidence: 99%